2021
DOI: 10.1021/acs.energyfuels.1c01999
|View full text |Cite
|
Sign up to set email alerts
|

Toward Separation and Characterization of Asphaltene Acid and Base Fractions

Abstract: Chemical inhibition of asphaltene deposition is considered a cost-effective way to prevent the harsh consequences of asphaltene instability in the produced crude. Thus, a careful screening of asphaltene inhibitors is crucial for an efficient prevention. However, the characteristics of asphaltenes such as their acid–base properties will influence the selection of an asphaltene inhibitor and the inhibition mechanism. Therefore, improved knowledge on asphaltene acidic and basic fractions is important. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Analogous to other crude oil fractions such as saturates or asphaltenes, the definition of NAs does not derive from the molecular standpoint. Commonly, naphthenic acids constitute part of the resin fractions in crude oils; however, certain acidic functionalities occur in asphaltene molecules. ,, For this reason, the behavior of acids at the water–oil interface originates from the contribution of different species with the carboxyl group in their structure. Figure shows a representation of the 5-β-cholanic acid, which is a NA model molecule commonly employed in experimental studies. ,, …”
Section: Water-in-crude Oil Emulsionsmentioning
confidence: 99%
“…Analogous to other crude oil fractions such as saturates or asphaltenes, the definition of NAs does not derive from the molecular standpoint. Commonly, naphthenic acids constitute part of the resin fractions in crude oils; however, certain acidic functionalities occur in asphaltene molecules. ,, For this reason, the behavior of acids at the water–oil interface originates from the contribution of different species with the carboxyl group in their structure. Figure shows a representation of the 5-β-cholanic acid, which is a NA model molecule commonly employed in experimental studies. ,, …”
Section: Water-in-crude Oil Emulsionsmentioning
confidence: 99%
“…Kelland et al developed a methodology for the fractionation of asphaltenes into their acidic, basic, and neutral components, applying the modified Ramljack method. 18 The results revealed that the composition of the acid fraction includes carboxylic acids, phenols, sulfoxide groups, and aliphatic groups, while the structure of the basic fraction contains amines and derivatives. Other authors have proposed alternative methodologies showing outstanding results but requiring the use of complex materials not commercially available, which disfavors the reproducibility of the results.…”
Section: Introductionmentioning
confidence: 97%
“…17 From elsewhere, according to the work of Siffert et al, there is a relationship between the flocculation of asphaltenes in a system of organic compounds and the surface electrical charge. 1 It implies that the distribution of all functional groups can be key in understanding the aggregation of asphaltenes from the perspective of electric charge, 18 considering that the net charge of an aggregate corresponds to the sum of charges provided by each functional group present in the molecules that make it up. For example, it can be generally stated that negatively charged asphaltenes tend to be dispersed by cationic amphiphiles, while positively charged amphiphiles tend to be dispersed by anionic amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the size of the aromatic core, the presence of heteroatoms on the core and the lateral chains as well as the length of the lateral chains must all be considered when choosing which model to use to depict the system. Although there is not a single, dominating form of asphaltene in all crude oil, it has been seen to contain both acid and base fractions, including phenols, carboxylic acids, sulfoxide groups, and aliphatic chains …”
Section: Introductionmentioning
confidence: 99%
“…Although there is not a single, dominating form of asphaltene in all crude oil, it has been seen to contain both acid and base fractions, including phenols, carboxylic acids, sulfoxide groups, and aliphatic chains. 16 The problem of asphaltene precipitation 17,18,27,28,19−26 and deposition 29−38 is well researched in the literature, with several control strategies such as mechanical and chemical options explored. The mechanical solutions involve the use of scrapers and pigs to remove the asphaltene deposit; 39−41 whereas, the chemical asphaltene control strategy involves the injection of fluids that have the propensity to interact with the asphaltene molecule, resulting in their increased solubility (dispersants) or prevention of its precipitation (inhibitors).…”
Section: ■ Introductionmentioning
confidence: 99%